Corpus pragmatics : a handbook (2014)
"Corpus linguistics is a long-established method which uses authentic language data, stored in extensive computer corpora, as the basis for linguistic research. Moving away from the traditional intuitive approach to linguistics, which used made-up examples, corpus linguistics has made a significant contribution to all areas of the field. Until very recently, corpus linguistics has focused almost exclusively on syntax and the lexicon; however corpus-based approaches to the other subfields of linguistics are now rapidly emerging, and this is the first handbook on corpus pragmatics as a field. Bringing together a team of leading scholars from around the world, this handbook looks at how the use of corpus data has informed research into different key aspects of pragmatics, including pragmatic principles, pragmatic markers, evaluation, reference, speech acts, and conversational organisation"--